Depression, cortisol and somatoform dissociative symptoms - Bob, Petr; Freybergh, P F; Jasova, Denisa; Susta, Marek; Pavlat, Josef; Zima, Tomas; Benakova, Hana; Bizik, Gustav; Svetlak, Miroslav; Vevera, Jan; Miklosko, Jozef; Hajek, Karel; et al. (Neuro endocrinology letters, 2008)
OBJECTIVE: According to recent findings neuroendocrine response related to dissociative symptoms is related to dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis but HPA axis functioning as related to dissociation is only partially understood. METHOD: With the aim to test the relationship between basal serum cortisol and dissociative symptoms measured as somatoform and psychic dissociation we performed clinical testing and biochemical analysis in 30 inpatients with diagnosis of unipolar depression (mean age 41.46, SD=13.68). RESULTS: The results show that cortisol as an index of HPA axis functioning manifests significant relationship to somatoform dissociative symptoms (r=-0.40; p=0.014). CONCLUSIONS: The result indicates relationship between HPA-axis reactivity and somatoform dissociative symptoms in unipolar depressive patients and suggests that somatoform dissociation presents a defense mechanism related to a passive coping response.
Keywords: dospělí; hydrokortison; depresivní poruchy; disociační poruchy; Humans; lidé středního věku; Middle Aged; Pituitary-Adrenal System; Hydrocortisone; Hypothalamo-Hypophyseal System; fyziologický stres; Surveys and Questionnaires; mužské pohlaví; Adult; Dissociative Disorders; Somatoform Disorders; průzkumy a dotazníky; somatoformní poruchy; systém hypotalamus-hypofýza; ženské pohlaví; systém hypofýza - nadledviny; lidé; Depressive Disorder; Male; Stress, Physiological; Female